Strengthening the Role of BPRS in Supporting MSMEs: Regulatory Perspective and Legal Challenges During and After the Pandemic - Ridwansyah, Ridwansyah; Supriyaningsih, Okta; Amrina, Dania Hellin (Universitas Islam Negeri Ar-Raniry Banda Aceh, 2025)
This study examines the strategic role of Sharia People's Financing Banks (BPRS) in supporting micro, small and medium enterprises (MSMEs) as a driver of Indonesia's economic recovery in the aftermath of the Covid-19 pandemic. Despite having a smaller share of total financing than Islamic Commercial Banks, BPRS plays a crucial role in reaching underserved microeconomic segments. Previous studies have shown that MSMEs are the backbone of the Indonesian economy, yet their access to financing remains limited. This research uses a qualitative method with a field approach through observation, in-depth interviews, and document analysis in selected regions. The findings show that BPRS financing has significantly contributed to MSME resilience and job creation, yet the sector still faces regulatory and policy challenges. Therefore, optimizing BPRS’ contribution requires legal frameworks that support risk mitigation, sustainability, and inclusive economic growth.